2013
DOI: 10.1002/mgg3.13
|View full text |Cite|
|
Sign up to set email alerts
|

A novel ERAP2 haplotype structure in a Chilean population: implications for ERAP2 protein expression and preeclampsia risk

Abstract: Single nucleotide polymorphisms (SNPs) in the endoplasmic reticulum aminopeptidase 2 (ERAP2) gene are associated with preeclampsia (PE) in different populations. rs2549782, a coding variant (N392K) that significantly affects substrate specificity, is in linkage disequilibrium (LD) with rs2248374, a marker SNP associated with ERAP2 protein expression in previously studied populations. As a result of nonsense-mediated RNA decay, ERAP2 protein is not expressed from the rs2248374 G allele. We previously reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…This functional variant is in strong linkage with SNP rs2248374. Apart from specific ethnic peculiarities, the N392 allelic variant is almost absent in the human populations because of its co-inheritance with the rs2248374 null-allele [84,85].…”
Section: Hla-b27 a Molecule With Two Faces: Protection From Viral Inmentioning
confidence: 99%
“…This functional variant is in strong linkage with SNP rs2248374. Apart from specific ethnic peculiarities, the N392 allelic variant is almost absent in the human populations because of its co-inheritance with the rs2248374 null-allele [84,85].…”
Section: Hla-b27 a Molecule With Two Faces: Protection From Viral Inmentioning
confidence: 99%
“…However, the strong linkage disequilibrium described above and ERAP2/PE association was not detected in a Chilean population, suggesting that N392 ERAP2 could be detected. However, we found that homozygosity for the T/T N392 ERAP2 (“gain-of-function”) allele is never detected in the mother or fetus in normal pregnancies in the Chilean population studied (n=528 dyads) [22]. One hypothesis to explain these observations is that “hyper” trimming capability for hydrophobic peptides alters the peptide and HLA class I repertoire in cells triggering immune activation, creating a non-permissive uterine environment for trophoblast cell/fetal survival [23].…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest common pathogenetic mechanisms involving the MHC-I bound peptidome. ERAP2, a related enzyme that acts in concert with ERAP1 (6,7), influences the susceptibility to BSCR (8), AS (although not necessarily in epistasis with HLA-B*27) (9), CrohnЈs disease (10), and preeclampsia (11)(12)(13). BSCR is a rare and severe form of bilateral posterior uveitis, showing a progressive inflammation of the choroid and retina, whose association with HLA-A*29 is the strongest for any disease and MHC.…”
mentioning
confidence: 99%